THE EFFECT OF PHOSPHORUS ADDITION ON THE ACTIVITY OF BISMUTH MOLYBDATE CATALYST FOR PARTIAL OXIDATION OF PROPYLENE TO ACROLEIN - Hamzah Fansuri; Gia Hung Pham; Sandra Wibawanta; Dong-ke Zhang (Indonesian Journal of Chemistry, 2010)
In order to examine the effect of phosphorus addition on the activity and selectivity of bismuth molybdate catalysts for partial oxidation of propylene to acrolein, three modes of phosphorus addition were performed. The three modes of Preparation were performed by (1) adding phosphorus into a-Bi2Mo3O12 to obtain Bi2PxMo3Oy, (2) inserting phosphorus on bismuth sites to obtain Bi2-xPxMo3Oy, and (3) inserting phosphorus on molybdenum sites to obtain Bi2PxMo3-xOy. Four major phases of bismuth phosphomolybdate were detected as the result of the phosphorus addition, namely a-Bi2Mo3O12, Bi9PMo12O52, MoO3, and BiPO4. Experimental results showed that the catalysts solely containing BiPO4 and/or MoO3 have very low activities for partial oxidation of propylene to acrolein. Meanwhile, catalysts containing a-Bi2Mo3O12 and Bi9PMo12O52, together with either MoO3 or BiPO4 showed on average the same activities as a-Bi2Mo3O12 and one of them (combination of a-Bi2Mo3O12, Bi9PMo12O52 and MoO3) has better performance than a-Bi2Mo3O12 at lower temperatures. The presence of the oxygen donor phase, i.e. BiPO4 and MoO3, are believed to play a key role for the high activities of bismuth-phosphomolybdate catalysts. However, at higher temperatures, the presence of oxygen donor reduces the catalyst selectivity to acrolein.